(untitled) (Revista de Ciências Agroveterinárias, 2016)
Weeds can cause significant agricultural yield losses, and the morning-glory species (Ipomoea spp.) has stood out in several crops. To control morning-glories we can use herbicides inhibiting the protoporphyrinogen IX oxidase enzyme in addition to glyphosate, a herbicide that this weed is intolerant to. The objective was to test the efficacy of application of isolates and mixtures of glyphosate (Roundup Original®) with carfentrazone-ethyl (Aurora®) and saflufenacil (Heat®) to control I. hederifolia in two weed growth stages. Treatments consisted of: isolated application of (i) carfentrazone-ethyl (50 and 75 mL l.h. ha-1), (ii) saflufenacil (35 and 50 g l.h. ha-1, and (iii) glyphosate (2 and 4 L l.h. ha-1; and mixtures of (iv) carfentrazone-ethyl+glyphosate and (v) saflufenacil+glyphosate (both in the lowest dose). Applications were performed on plants with 6-8 and 15-20 leaves, maintaining herbicide-free checks for both plant growth stages. Mixture of carfentrazone-ethyl and saflufenacil with glyphosate increases the efficacy of control of I. hederifolia, compared to herbicide isolate applications. Mixture of 2 L ha-1 + 50 mL ha-1 of glyphosate+carfentrazone-ethyl provides more efficient and faster control of I. hederifolia, mainly when the plants have 6-8 leaves.